2019
DOI: 10.1103/physreva.100.013620
|View full text |Cite
|
Sign up to set email alerts
|

Static-response theory and the roton-maxon spectrum of a flattened dipolar Bose-Einstein condensate

Abstract: Important information for the roton-maxon spectrum of a flattened dipolar Bose-Einstein condensate is extracted by applying a static perturbation exhibiting a periodic in-plane modulation. By solving the Gross-Pitaevskii equation in the presence of the weak perturbation we evaluate the linear density response of the system and use it, together with sum rules, to provide a Feynman-like upperbound prediction for the excitation spectrum, finding excellent agreement with the predictions of full Bogoliubov calculat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…On the other hand, quantum gases with magnetic dipole-dipole interaction (DDI), especially the BECs with DDI, have also drawn much attention both experimentally [35][36][37][38] and theoretically [39][40][41][42][43][44][45][46][47][48] in recent years. Relevant studies on spinor BECs with DDI have shown that the interplay between the short-range spin-exchange interaction and the long-range anisotropic DDI can lead to rich topological defects, spin textures and spin dynamics [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, quantum gases with magnetic dipole-dipole interaction (DDI), especially the BECs with DDI, have also drawn much attention both experimentally [35][36][37][38] and theoretically [39][40][41][42][43][44][45][46][47][48] in recent years. Relevant studies on spinor BECs with DDI have shown that the interplay between the short-range spin-exchange interaction and the long-range anisotropic DDI can lead to rich topological defects, spin textures and spin dynamics [39,40].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, quantum gases with magnetic dipole-dipole interaction (DDI), especially the BECs with DDI, have also drawn much attention both experimentally [35][36][37][38] and theoretically [39][40][41][42][43][44][45][46][47][48] in recent years. Relevant studies on spinor BECs with DDI have shown that the interplay between the short-range spin-exchange interaction and the long-range anisotropic DDI can lead to rich topological defects, spin textures and spin dynamics [39,40].…”
Section: Introductionmentioning
confidence: 99%